Fly ash used as a reinforcing and flame-retardant filler in low-density polyethylene - Porąbka, A.; Jurkowski, K.; Laska, J. (Polimery, 2015)
In this study, the possibility to modify low density polyethylene (PE-LD) with fly ash (FA) was tested. Four series of PE-LD composites filled with 1, 5, 20 or 50 wt % of FA were prepared by injection molding. The samples in each of the series differed in particle size of the filler used (0—15 µm, 15—30 µm, 30—60 µm). The influence of amount and the particles size of filler on morphology, mechanical properties, thermal stability and flammability of the composites were investigated. The results show that composites with the addition of FA in the amount up to 20 wt % are characterized by good mechanical properties and processability, and also smaller than the pure PE-LD, flammability.